The farmer's bride - Fuller, Kathleen (Fuller, Kathleen. Amish brides of Birch Creek., 2019)
"Bestselling and award-winning author Kathleen Fuller returns to the Amish community of Birch Creek in this charming tale of falling in love while pursuing the dreams of your heart"--